KLF 15 Works as an Early Anti-Fibrotic Transcriptional Regulator in Ang II-Induced Renal Fibrosis via Down-Regulation of CTGF Expression - Xiangchen Gu; Dechao Xu; Lili Fu; Yi Wang; Changlin Mei; Xiang Gao (Karger Publishers, 2017)
Background/Aims: Angiotensin II (Ang II) has been regarded as an important profibrogenic cytokine in renal fibrosis. Krüppel-like factor 15 (KLF15) has been identified as an important negative transcription factor in renal fibrosis. However, little is known about the role of KLF15 in Ang II-induced renal fibrosis. Methods: In this study, we randomized mice into a control group, Ang II group or Ang II plus losartan group. KLF15 expression was examined with real-time PCR and immunofluorescence in these groups. In vitro, KLF15 expression was examined by Western blot in rat renal fibroblasts (NRK-49F) stimulated with Ang II, and the effect of altered KLF15 expression on the regulation of the profibrotic factor connective tissue growth factor (CTGF) was further explored with co-immunoprecipitation (CoIP) and chromatin immunoprecipitation (ChIP) analyses. Results: Compared with the control group, the murine model of Ang II-induced renal fibrosis demonstrated a significant decrease in renal KLF15 expression at 4 weeks and presented with progressive renal fibrosis at 6 weeks. Meanwhile, losartan, an angiotensin type 1 (AT1) receptor antagonist, effectively prevented the down-regulation of KLF15 expression induced by Ang II infusion. In vitro, NRK-49F cells stimulated with Ang II exhibited a significant decrease in KLF15 expression, accompanied by a marked increase in the expression of profibrotic factors and in the production of extracellular matrix. The up-regulation of CTGF expression induced by Ang II stimulation was inhibited by KLF15 overexpression in NRK-49F cells, and losartan treatment prevented the down-regulation of KLF15 expression and the up-regulation of CTGF expression induced by Ang II stimulation. Furthermore, CoIP and ChIP assays revealed that the transcription regulator KLF15 directly bound to the co-activator P/CAF and repressed its recruitment to the CTGF promoter. Conclusions: Ang II down-regulates KLF15 expression via the AT1 receptor, and KLF15 is likely to inhibit Ang II-induced CTGF expression by repressing the recruitment of the co-activator P/CAF to the CTGF promoter.